Exploring concepts of ethno-mathematics to introduce the local culture and its values for higher education students - Cesaria, Anna; Adnan, Mazlini; Kemal, Edwar; Rismen, Sefna; Ramadoni, Ramadoni; Delyana, Hafizah (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study aims to explore higher education students’ perspectives on the ethno-mathematics course as a means to introduce local culture and its values. The research specifically examines the ethno-mathematical concepts represented in Rumah Gadang, a traditional building in Batusangkar, West Sumatra. Method: A qualitative approach with an ethnographic design was used in this research. Data were collected from 35 students enrolled in the ethno-mathematics course at a private university through qualitative questionnaires. In addition, two cultural experts were interviewed using semi-structured interview questions. The data were analyzed using content analysis to identify key themes related to shapes, space, measurement, and arithmetic as reflected in Rumah Gadang. Findings: The results show that all students agreed on the importance of integrating ethno-mathematics in their learning. The students demonstrated increased interest and appreciation for mathematics when it was linked to cultural contexts. They recognized the relevance of mathematical concepts such as shape, space, measurement, and arithmetic in the design and philosophy of Rumah Gadang. Insights from interviews with cultural experts further confirmed that Rumah Gadang embodies mathematical reasoning that is closely connected to cultural identity and local values. Significance: The research demonstrates that ethno-mathematics courses can effectively foster cultural appreciation and help preserve local heritage among university students. This encourages students to see mathematics as not only a universal science but also a reflection of cultural traditions. The study highlights the value of using local cultural artifacts as authentic contexts in mathematics education, with implications for curriculum development that supports both academic achievement and cultural preservation.